ISOLATION AND IDENTIFICATION OF PESTE DES PETITS RUMINANTS VIRUS BY CELL CULTURE AND IMMUNOCAPTURE ENZYME LINKED IMMUNOSORBENT ASSAY - S. Bahadar; A. A. Anjum; M. D. Ahmad; A. Hanif (Journal of Animal and Plant Sciences, 2009)
Thirty tissue samples each of Necrotic debris in buccal mucosa, nasal discharges, ocular discharges and lymph nodes were collected from clinical cases and checked for Peste des Petits Ruminants (PPR) virus using Immunocapture Enzyme Linked Immunosorbent Assay (IC ELISA). The IC ELISA showed presence of PPR antigen 43.3% (13/30) in buccal mucosa samples, 36.6% (11/30) in nasal discharges, 40% (12/30) in ocular discharges and 80% (24/30) in lymph nodes. Overall percentage of PPR antigen in all different samples detected by IC ELISA was 50%. Samples found positive for Vero cell cultures were subjected to antigen detection by using IC ELISA. Out 30 buccal mucosa samples, 30 nasal discharges, 30 ocular discharges and 30 lymph nodes 11, 9, 9 and 22 samples were found positive respectively. Thus an overall 41% samples were found positive by cell culture isolation and IC ELISA. Lymph nodes were found to be the best organ for identification of PPR antigen by IC ELISA.
Keywords: PPR; IC ELISA; Cell Culture